Insight into the metabolic potential and ecological function of a novel Magnetotactic Nitrospirota in coral reef habitat - Zhao, Yicong; Zhang, Wenyan; Pan, Hongmiao; Chen, Jianwei; Cui, Kaixuan; Wu, Long-Fei; Lin, Wei; Xiao, Tian; Zhang, Wuchang; Liu, Jia (Frontiers in Microbiology, 2023)
Magnetotactic bacteria (MTB) within the Nitrospirota phylum play important roles in biogeochemical cycles due to their outstanding ability to biomineralize large amounts of magnetite magnetosomes and intracellular sulfur globules. For several decades, Nitrospirota MTB were believed to only live in freshwater or low-salinity environments. While this group have recently been found in marine sediments, their physiological features and ecological roles have remained unclear. In this study, we report, for the first time, the presence of a population of Nitrospirota MTB in a coral reef area in the South China Sea. Both phylogenetic and genomic analyses revealed it as representative of a novel genus, named as Candidatus Magnetocorallium paracelsis XS-1. The cells of XS-1 are small and vibrioid-shaped, and have bundled chains of bullet-shaped magnetite magnetosomes, sulfur globules and cytoplasmic vacuole-like structures. Genomic analysis revealed that XS-1 has the potential to respire sulfate and nitrate, and utilize the Wood–Ljungdahl pathway for carbon fixation. XS-1 has versatile metabolic traits that make it different from freshwater Nitrospirota MTB, including Pta-ackA pathway, anaerobic sulfite reduction and thiosulfate disproportionation. XS-1 also encodes both the cbb3-type and the aa3-type cytochrome c oxidases, which may function as respiratory energy-transducing enzymes respectively under high oxygen conditions and anaerobic or microaerophilic conditions. XS-1 has multiple copies of circadian related genes in response to variability in coral reef habitat. Our results implied that XS-1 has a remarkable plasticity to adapt the environment and can play a beneficial role in coral reef ecosystems.